2020
DOI: 10.22159/ijcpr.2020v12i4.39050
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals in the Treatment of Arthritis: Current Knowledge

Abstract: The objective of the present review is to evaluate the therapeutic potential of phytochemicals against arthritis, which is asymptomatic disorder of chronic joint inflammation followed by swelling and pain. Here, we discussed about the anti-arthritic activity of many phytomolecules such as Norisoboldine, Berberine, Triptolide, Hesperidin Hesperidin, Madecassocide, Hydroxy napthoquinone, Ginsenoside, Cryptotanshinone, Kirenol, Thymoquinone, Chlorogenic acid, Curcumin, Bromelain, Andrographolide and Allicin. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Medicinal plants are valuable natural resources that are considered by the advanced countries of the world as raw materials to become safe medicines for human diseases (Bose et al, 2020;Bhattacharya et al, 2020). The present study was designed to assess the antioxidant effect of methanolic extract of F. vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants are valuable natural resources that are considered by the advanced countries of the world as raw materials to become safe medicines for human diseases (Bose et al, 2020;Bhattacharya et al, 2020). The present study was designed to assess the antioxidant effect of methanolic extract of F. vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…Around 20 million people around the world are estimated to be prone to RA conditions (Safiri et al, 2019). The currently available medications are shown to cause a lot of adversities such as heartburn, anemia, abdominal pain, peptic ulcer, gastrointestinal bleeding, cataracts, high/low blood pressure, insomnia, muscle atrophy, osteoporosis, body weight gain, and immunity loss upon continuous usage (Bhattacharya et al, 2020;Al-Lawati et al, 2020, Fischer et al, 2020. So, safe and efficient natural agents having the ability to manage or to inhibit the progress of the RA conditions are of great significance.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have confirmed that the isoquinoline alkaloid norisoboldine (NOR) (compound 12 in Table 2 ) from LA-R is the most representative active compound and possesses outstanding anti-arthritis activity ( 82 ). In CIA rats, oral NOR (10, 20, and 40 mg/kg) significantly decreased the swelling of paws, arthritis index scores and elevated the lowered body weights of rats.…”
Section: Pharmacologymentioning
confidence: 99%
“…As shown in Table 1 and Figure 2, modern phytochemistry studies reveal that the sesquiterpenoids isolated from L. aggregata are mainly featured as monomer-, dimer-, and hybrid forms. The sesquiterpenoid monomers include eudesmane- , lindenane- , germacrane- (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69), elemane-(70-73), guaiane- (74)(75)(76), cadinane- (77)(78), copane- (79), eremophilane- (80), and other types (81)(82)(83)(84) (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). So far, the sesquiterpenes of L. aggregata account for more than half ...…”
Section: Sesquiterpenoidsmentioning
confidence: 99%